(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The polysaccharide complex (PSC) from the aerial parts and roots of Acanthophyllum subglabrum (AS) was isolated and studied. The AS PSC contains 83.64±5.93% hexoses, 21.22±2.48% uronic acids, 2.27±0.27% protein, neutral monosaccharides are represented by glucose, galactose, arabinose (molar ratios: 1.2:5.5:1.0), and trace amounts of xylose were also present. Four main components were isolated using ion-exchange chromatography. Four main components were isolated using ion-exchange chromatography. The structure of the obtained polysaccharides (PS) 1-4 was characterized using physicochemical methods, such as IR spectroscopy, high-performance size-exclusion and gas-liquid chromatography, and reactions with Congo red. It was found that all PS are characterized by different contents of hexoses (from 32.46±2.63 to 83.64±5.93%), uronic acids (from 7.56±0.17 to 21.22±2.48%) and an insignificant admixture of protein (from 0.75±0.13 to 2.28±0.17%). The obtained polysaccharides are highly homogeneous samples, varying in monomeric composition. The major component of PSAS-1-4 is represented by galactose.